ELIGIBILITY STATUS KAWAKAWA (EUTHYNNUS AFFINIS CANTOR, 1849) FROM LOMBOK STRAIT AND INDIAN OCEAN SOUTHERN SUMBAWA - Fathurriadi (Fakultas Perikanan Universitas 45 Mataram, 2020)
Little tuna or Kawakawa (Euthynnus affinis) or tongkol banyar (Indonesian) are one species of neritic tuna landed in Bangko-Bangko (Lombok Barat District) and Labangka (Sumbawa District). This study aims to determine the feasibility status of kawakawa catch with fisheries biology parameter approach, namely growth pattern (b), condition factor (K), length captured (Lc), and length maturity (Lm). Survey methods and sampling, documentation, interview, and observation techniques were chosen to collect data that were processed quantitatively. Comparative data analysis to obtain justification, relevance and/or contradiction between results and status with theory and policy. Kawakawa are caught by fishermen in Lombok Strait and Indian Ocean in south Sumbawa using surface longlines and gillnets, which are selective fishing gear. Based on the parameters of the condition factor, many of kawakawa have flesh (K>1.0) so that their status is worth catching and worth selling.  The growth pattern parameter is hyper allometric (b>3.0), so that the status is worth catching and worth selling. The technology performance of catching kawakawa in the study location has a dangerous status (Lc/Lm<1.0), which means that the kawakawa captured have never maturity have never matured. That fishing technology of kawakawa is not environmentally friendly in terms of fish resources conservation, especially in preservation and protection. Thus the kawakawa in Lombok Strait and Indian Ocean in south Sumbawa were not eligible to be captured during February-July.